Studi tentang Gaya Kepemimpinan dan Tingkat Pendidikan serta Pengaruhnya terhadap Kinerja Karyawan dalam Perspektif Islam - Cindy Maharati (Sekolah Tinggi Ilmu Ekonomi Syariah Riyadlul Jannah Mojokerto, 2021)
The purpose of this study was to examine and analyze the simultaneous, partial and dominant effect of the variable leadership style and education level on employee performance. This research is explanatory (explaining) is